2018
DOI: 10.1016/j.ajhg.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

OTUD7A Regulates Neurodevelopmental Phenotypes in the 15q13.3 Microdeletion Syndrome

Abstract: Copy-number variations (CNVs) are strong risk factors for neurodevelopmental and psychiatric disorders. The 15q13.3 microdeletion syndrome region contains up to ten genes and is associated with numerous conditions, including autism spectrum disorder (ASD), epilepsy, schizophrenia, and intellectual disability; however, the mechanisms underlying the pathogenesis of 15q13.3 microdeletion syndrome remain unknown. We combined whole-genome sequencing, human brain gene expression (proteome and transcriptome), and a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
98
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 86 publications
20
98
0
Order By: Relevance
“…Here, we report the first case of a homozygous missense variant (NM_130901.2:c.697C>T, p.(Leu233Phe)) in OTUD7A and related proteasome dysfunction found in a patient with severe global developmental delay, language impairment and epileptic encephalopathy. Based on our finding and recent literature, this gene variant may have a significant role in chromosome 15q13.3 microdeletion syndrome, associated with a wide range of neurodevelopmental disorders.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Here, we report the first case of a homozygous missense variant (NM_130901.2:c.697C>T, p.(Leu233Phe)) in OTUD7A and related proteasome dysfunction found in a patient with severe global developmental delay, language impairment and epileptic encephalopathy. Based on our finding and recent literature, this gene variant may have a significant role in chromosome 15q13.3 microdeletion syndrome, associated with a wide range of neurodevelopmental disorders.…”
Section: Introductionsupporting
confidence: 78%
“…In support of the findings described in mice, Uddin et al also reported a 5‐year‐old female, with global DD and a genetic deletion that spanned BP4‐BP5 encompassing OTUD7A , but not CHRNA7 , as well as an ASD male individual carrying an inframe deletion in OTUD7A (NM_130901.2( OTUD7A ):c.1474_1482del, p.(Asn492_Lys494del)). The inframe deletion was not inherited from the healthy parents and was also present in the affected brother.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations